Autocratic Legalism through Anti-Corruption Strategies and Agencies: A Case Study of Nigeria - Assim, Usang; Adeyemo, Deborah D (Journal of Anti-Corruption Law, 2025)
One of the hallmarks of the transition to constitutional democracy in Nigeria is the consolidation of an overarching anti-corruption strategy. After several years of successive military rule, Nigeria transited to a democratic dispensation in 1999. On the heels of this transition was the institution of the crusade against corruption which is often blamed as the progenitor of all the ills in Nigeria. In over two decades after the transition and the commencement of the anti-corruption crusade, it would seem that the anti-corruption strategies of the different administrations are targeted at perceived opponents and influenced by the private interests of political elites. The paper examines the operation of anti-corruption agencies (ACAs) as tools to entrench autocratic legalism in Nigeria. It interrogates the narrative that successive democratic administrations manipulate ACAs to perpetuate oppression and selectively apply anti-corruption mechanisms. The paper is purely doctrinal and adopts a desktop legal research approach. The paper examines whether purported anti-corruption strategies by different administrations are exploited to mask their rent-seeking tendencies. The political manipulations of prosecutorial authorities, selective prosecution by ACAs, indiscriminate application of plea bargain and abuse of court process do not only undermine anti-corruption efforts but subtly perpetuate autocratic legalism in Nigeria.